A Review of Entomopathogenic Fungi of Iraq - Alhadidi, Sanaa Nagem Abed (Iraqi Journal of Science, 2023)
Insect pest management has been dominated by the use of synthetic pesticides since early 1950s. However, lately this control method is not widely accepted due to an increase in environmental awareness, food safety concerns and the increasing number of insecticide-resistant species. In Iraq, the chemical insect pest control is still a dominant control method regardless of the increased pressure to replace it gradually with environment friendly alternatives such as predators, parasitoids, nematodes and entomopathogenic fungi. In Iraq, there is an increasing volume of research that has used different genus and species of entomopathogenic fungi for controlling several agricultural pests. However, these efforts are not yet reflected in the industry. In this short review article, a detailed summary of the research that has been done with entomopathogenic fungi in Iraq since 2000 is given and a brief discussion of the potential of using entomopathogenic fungi on a large scale in Iraq, its challenges, and recommendations is presented.